2017
DOI: 10.1159/000479997
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 is Involved in Vitamin D-Induced Chondrogenic Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells by Regulating the ERK/JNK Pathway

Abstract: Background/Aims: Osteoarthritis (OA) is characterized by degradation of cartilage, sole cell type of which is chondrocytes. Bone marrow-derived mesenchymal stem cells (BMSCs) possess multipotency and can be directionally differentiated into chondrocytes under stimulation. This study was aimed to explore the possible roles of vitamin D and transforming growth factor-β1 (TGF-β1) in the chondrogenic differentiation of BMSCs. Methods: BMSCs were isolated from femurs and tibias of rats and characterized by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…However, it has already been outlined from several stem cell systems that the ERK pathway is involved in chondrogenic differentiation [Jiang et al, 2017;Wang et al, 2017a;Wu et al, 2018], and plays a vital role in the proliferation of MSCs [Kim et al, 2015;Yang et al, 2017]. Therefore, we investigated the effect of hyperosmolarity on the activation of the ERK pathway, and the regulatory role of this pathway on the proliferation and chondrogenic differentiation of NP-MSCs under the hyperosomotic conditions of IVD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, it has already been outlined from several stem cell systems that the ERK pathway is involved in chondrogenic differentiation [Jiang et al, 2017;Wang et al, 2017a;Wu et al, 2018], and plays a vital role in the proliferation of MSCs [Kim et al, 2015;Yang et al, 2017]. Therefore, we investigated the effect of hyperosmolarity on the activation of the ERK pathway, and the regulatory role of this pathway on the proliferation and chondrogenic differentiation of NP-MSCs under the hyperosomotic conditions of IVD.…”
Section: Discussionmentioning
confidence: 93%
“…However, there is a paucity of data about the influence of hyperosmolarity of IVD on the proliferation and chondrogenic differentiation of NP-MSCs. The extracellular signal-regulated kinase (ERK) pathway is a mitogen-activated protein kinase (MAPK) pathway, which is involved in the chondrogenic differentiation [Jiang et al, 2017;Wang et al, 2017a;Wu et al, 2018] and proliferation [Kim et al, 2015;Yang et al, 2017] of MSCs. To the best of our knowledge, no literature is available that describes the regulatory role of ERK in the proliferation and chondrogenic differentiation of NP-MSCs under the hyperosmotic condition of IVD.…”
mentioning
confidence: 99%
“…Jiang et al . indicated that Vitamin D remarkably promoted BMSC viability, migration and chondrogenic differentiation 32 . In this work, we developed an aging rat model induced by D-gal, which was now recognized as an inducer of aging reagents that was accelerated senescence in rats 33 .…”
Section: Discussionmentioning
confidence: 96%
“…Joint articular cartilage degeneration plays a fundamental role in the pathogenesis of osteoarthritis (OA), which is characterized by joint pain, stiffness, and limited mobility [2]. Bone marrow-derived mesenchymal stem cells (BMSCs) have been widely used in tissue regeneration due to their potential to differentiate into multiple cell lineages including osteocytes, adipocytes, and chondrocytes [3, 4]. However, BMSC-based cartilage tissue regeneration biochemically and biomechanically adequate for clinical use has not been successful and is hindered by chondrogenic induction and hypertrophy.…”
Section: Introductionmentioning
confidence: 99%